A NUMERICAL STUDY OF CORRUGATED SIERPINSKI CARPET ON SOLAR DRYER - Lohdy Diana Diana; Arrad Ghani Safitra; Eli Novita Sari; Firman Yunan Saputra; Muhammad Yusuf Febrian Putra; Mutia Ayu Agustina; Ar Rayyan Ikhsan Syahputra (Logic : Jurnal Rancang Bangun dan Teknologi, 2026)
Solar dryers have problems with low heat transfer performance and uneven temperature distribution, resulting in low efficiency. The efficiency of solar dryers depends on the design of the absorber plate, namely how much it can absorb solar heat. This study applies a Siepinski carpet with a complex structure and large dimensions, resulting in iterations called fractals. This study aims to improve the efficiency of solar dryers as an alternative to the negative impact of falling tomato prices, to determine the effect of the Siepinski Carpet Corrugated fractal distance on the performance of solar dryers in terms of heat transfer, to compare corrugated absorber plates with 3 siepinski carpet corrugated based on variations in the fractal ratio (RF), namely the ratio of the fractal center distance to the fractal length RF = 1, RF = 0.75, and RF = 0.6, on the performance of solar dryers, as well as to determine the distribution of temperature, pressure, and air flow velocity in the collector using the Computational Fluid Dynamics (CFD) simulation method. This study used simulation methods that was conducted in a laboratory. In conclusion, the fractal ratio strongly influences airflow behavior and temperature distribution, where overly dense or overly open configurations enhance heat transfer, while intermediate obstruction can reduce thermal performance. Among the cases studied, RF = 1 and RF = 0.6 provide more effective and consistent heat transfer compared to RF = 0.75.